SELEKSI DAN EVALUASI PERUBAHAN WARNA HASIL PERSILANGAN JAGUNG UNGU DAN JAGUNG KUNING MANIS PADA GENERASI F2, F3 DAN F4 - Mustakim; Maemunah; Sakka Samudin; Yusran (FAKULTAS PERTANIAN UNIVERSITAS ALKHAIRAAT, 2020)
Selection and evaluation of the progress of crosses is important to obtain the percentage change and success of crosses. This study aims to evaluate the percentage change in carnelian color up to the F4 generation and the selection progress in the F4 generation. The research was conducted from August 2017 to August 2020 in Kalukubula village, Sigi Regency, Palu, Central Sulawesi Province. This study was structured using a randomized block design with five carnelian color treatments that were repeated five times. This study used a mass selection method by selecting the carnel color according to the treatment (purple, yellow, white, purple dominant yellow and white dominant purple). Each treatment was planted in one plot for each generation. The seeds were planted using an isolation time of 21 DAS. The results showed that there were three color carnelian characters that experienced an increase in the percentage of color up to the F4 generation, namely Purple (27.68% -70.39%), White Dominant Purple (1.52% -16.91%) and White (5.40% -91.22%), and There are two carnelian color characters that experience a decrease in the percentage of color in the F4 generation, namely Yellow (68.14% -64.31%) and Purple Dominant Yellow (27.00%-5.22%). The character of purple, white, dominant purple and white carnelian color had a significant increase in heritability values ​​in the F4 population, and had an expected genetic progression value (36.94%, 17.56%, 53.55%) and positive selection progress in the F4 generation.